Asymmetric Information, Transaction Costs, and Farmers Decision To Participate In Tobacco Voor-Oogst Kasturi Contract Farming - M Rondhi; Rokhani Rokhani; Anik Suwandari; Kintani Sekarkundi Lahitani; Ahmad Fatikhul Khasan; Dian Permata Sari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Contract farming is a vital tool to connect farmer and industry. However, contracts participation between tobacco farmers and tobacco leaf supplier (TLS) was still low even though the benefit of the contract is enormous. The low participation was related to factors that affect the contract, demographics, farm characteristic, and other related factors. However, farmer participation on the contract was still low. Besides, contracts initially became a tool to prevent market failure since it regulated how economic actors acted against others causing transaction costs (TC) due to asymmetric information that made the contract not function ideally. Therefore, this study attempts to (1) explain factors underlying farmer decision to participate in contract farming (CF), (2) explain asymmetric information. Respondents in this study were 100 respondents consisting of 50 tobacco contract farmers, and 50 independent farmers. This study applied logistic regression analysis to analyze factors affecting farmer participation in CF. Besides, the New Institutional Economy approach was exerted to analyze asymmetric information on product transfer from farmer to TLS. The results showed that factors that significantly influenced tobacco farmers' decision-making to participate in CF are farming experience, land size, risk aversion level (RAL), the certainty of price, and source of capital. Asymmetric information caused adverse selection and moral hazard. About 30% of farmers had sold products to other parties (other TLSs and middleman), and 8% of farmers had applied pesticides that TLS prohibited. Contracts that were not ideal due to asymmetric information must be re-enforced by using additional costs called transaction costs, divided into three types, (1) search and information costs, (2) cost to design, negotiate and conclude and (3) the monitor and contract enforcement costs. Monitoring costs had the potential to absorb the most considerable portion compared to the other types of transaction costs. The greater the asymmetric information generated, the greater the transaction costs incurred.